The Evaluation of the Impact of Implementing Organizational Culture on Employee Innovative Behavior - Handayani, Widya; Pendrian, Okder (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This research explores the impact of organizational culture on innovative behavior at PT XYZ, a multinational motorcycle manufacturing company. The goal is to understand how the company's organizational culture contributes to fostering innovative behavior among its employees, ultimately helping PT XYZ maintain its competitiveness in the business environment. Methodology/approach – Using qualitative methods, data were collected through interviews with employees and supported by secondary sources. Findings – The findings reveal that PT XYZ's organizational culture positively influences innovative behavior through initiatives like